FASILITAS OBJEK WISATA AIR PANAS CAGAR ALAM RIMBO PANTI DI KECAMATAN PANTI KABUPATEN PASAMAN PROVINSI SUMATERA BARAT - Wulan Fitri Yeni; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Rimbo Panti hot springs tourist attraction is one of the tourist attractions in Pasaman Regency. This study aims to determine the condition of the facility, the government's plan to develop facilities to increase tourist visits and to find out the inhibiting factors faced by the government in developing facilities at the Rimbo Panti hot springs tourist attraction in Pasaman Regency, West Sumatra Province. This study used descriptive qualitative method. Data collection techniques used are observation, interviews and documentation. Based on the results of research conducted, the condition of some of the existing facilities at this tourist attraction is not good so that it has an impact on the number of tourist visits. The subjects of this study were the Youth Sports & Culture Tourism Office and visitors to the Rimbo Panti hot springs tourist attraction. Keywords : Facilities, Hot Water, Rimbo Panti